Winning a voice in educational administration : study of women working in middle management : a thesis submitted in partial fulfilment of the requirements for the degree of Master of Educational Administration - Court, Marion R. (Massey University, 1989)
This study examines a group of women working in educational middle management in both primary and secondary schools in a provincial area of New Zealand. The focus is the inequalities of power in gender relations within the women's home and school situations. It examines the ways these relations contribute to theories explaining the persisting low status of women in educational management. The theoretical framework draws on critical theory and cultural studies, along with feminist critiques of androcentric administration theories and practices. These critiques call for a reconstruction of theories of leadership to take account of women's perspectives and values. A questionnaire survey was used to document the teaching service of 30 women who took part in a 'self-help' management training strategy. Alongside the career constraint of time out of full-time service for child rearing, the women identified discriminatory attitudes and practices that relate to perceptions that women should have primary responsibility for caring and nurturing within both their home and paid work situations. These attitudes are woven into the structures, policies and practices of educational institutions in ways that can limit the opportunities of all women teachers. Six of these women participated in case study interviews which investigated the sexual division of labour at work and in the home. As a consequence of the sexual division of labour and a hegemonic linking between 'masculinity' and authority, they were involved in struggles to 'win' their authority and establish the right to lead as educational administrators. The study also investigated the place of anger in the women's development of a sense of autonomy. It concludes that the caring and nurturing responsibilities of women in the home reinforced an affiliative style of educational management in the workplace, which emphasised shared decision making and equal power relations.
Keywords: Women in educational administration; Educational administration; Educational management; Middle management; Educational administrators